Improved survival with enasidenib versus standard of care in relapsed/refractory acute myeloid leukemia associated with IDH2 mutations using historical data and propensity score matching analysis. (24th August 2021) - de Botton, Stéphane; Brandwein, Joseph M.; Wei, Andrew H.; Pigneux, Arnaud; Quesnel, Bruno; Thomas, Xavier; Legrand, Ollivier; Recher, Christian; Chantepie, Sylvain; Hunault‐Berger, Mathilde; Boissel, Nicolas; Nehme, Salem A.; et al.
Abstract: Background: The present study evaluated the relative survival benefits associated with enasidenib and current standard of care (SoC) therapies for patients with relapsed/refractory (R/R) acute myeloid leukemia (AML) and an isocitrate dehydrogenase 2 ( IDH2) mutation who are ineligible for hematopoietic stem cell transplantation (HSCT). Methods: Propensity score matching (PSM) analysis compared survival outcomes observed with enasidenib 100 mg daily in the phase I/II AG221‐C‐001 trial and SoC outcomes obtained from a real‐world chart review of patients in France. Results: Before matching, enasidenib ( n = 195) was associated with numerically improved overall survival (OS) relative to SoC ( n = 80; hazard ratio [HR], 0.82; 95% confidence interval [CI], 0.61–1.11). After matching and adjusting for covariates ( n = 78 per group), mortality risk was significantly lower with enasidenib than with SoC (HR, 0.67; 95% CI, 0.47–0.97). The median OS was 9.26 months for enasidenib (95% CI, 7.72–13.24) and 4.76 months for SoC (95% CI, 3.81–8.21). Results remained robust across all sensitivity analyses conducted. Conclusions: PSM analyses indicate that enasidenib significantly prolongs survival relative to SoC among patients with R/R AML and an IDH2 mutation who are ineligible for HSCT. Future prospective studies are needed to validate these findings using other data sources and to assess the comparative efficacy of enasidenib for other treatment outcomes. Abstract : Overall survival was improved with enasidenib compared with SoC. Enasidenib may be an important advance in treatment for patients with R/R acute myeloid leukemia associated with IDH2 mutations who are ineligible for hematopoietic stem cell transplantation.